The western time of ancient history historiographical encounters with the Greek and Roman pasts - Lianeri, Alexandra (Cambridge University Press, 2011)
"This book examines the conceptual and temporal frames through which modern Western historiography has linked itself to classical antiquity. In doing so, it articulates a genealogical problematic of what history is and a more strictly focused reappraisal of Greek and Roman historical thought. Ancient ideas of history have played a key role in modern debates about history writing, from Kant through Hegel to Nietzsche and Heidegger, and from Friedrich Creuzer through George Grote and Theodor Mommsen to Momigliano and Moses Finley; yet scholarship has paid little attention to the theoretical implications of the reception of these ideas. The essays in this collection cover a wide range of relevant topics and approaches and boast distinguished authors from across Europe in the fields of classics, ancient and modern history and the theory of historiography"--